PENGARUH HASIL PENGUMUMAN PEMILIHAN PRESIDEN 2019 TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Tita Nurvita (ESENSI: Jurnal Manajemen Bisnis, 2019)
This study aims to examine the information content of the stock price on the Indonesia Stock Exchange around the date of the announcement of the results of the presidential election by the General Election Commission in May 2019.The data used in this study is the data of three sector stock trading transactions: transportation, infrastructure and telecommunications. The reason for choosing the sample is related to the vision of Candidate President Jokowi, one of which is to focus on the development of fields that support investment progress. The research method used is event studies with the first stage determining event windows i.e. +30 after the event date and -30 before the event date. Data is processed to find the average abnormal return value which indicates the information content around the date of observation.The results showed that there was good news on the +9 day after the announcement of the presidential election results and the 5th day before the election announcement date.Keywords: abnormal return, cumulative abnormal return, event studies, event windows, good news